Priced to care: Factors underpinning missed care. (September 2016) - Harvey, Clare; Willis, Eileen; Henderson, Julie; Hamilton, Patti; Toffoli, Luisa; Verrall, Claire; Blackman, Ian; Abery, Elizabeth
This article examines missed care through dialogues examining the perceptions of nurses in regard to missed care occasions. Using a critical discourse analysis (CDA), the study explores the truth claims of participants who describe the challenges they encounter in daily attempts to deliver what they consider effective patient care. These are compared to the mandates of state and organisational policy prescribing clinical practice. The boundaries of tension that are expressed by nurses within the milieu of missed care are explored through in-depth interviews. CDA is interested in social organisation and the interplay of people's activities within it, the focus being on how they construe and internalise such activity. Nurses' perceptions and realities become central to any investigation because they are often organised by more than their own intentions or motivations, with influences such as professional standards or organisational rules subconsciously locating their reality. Instead of identifying occasions of omitted care, nurses spoke of constraints related to budget, staffing, skill mix and mandated policy as constraining their ability to complete care activities. Factors emerged that suggest that missed care is the consequence of routinised and standardised practice, cited as cost effective care, at the expense of professional autonomy.